From Tributary Ties to BRI Connectivity: Historical Continuity and Asymmetric Relation in China-Laos Cooperation - Tania Adarani; Tuty Nur Mutia Muas (Published by Confucius Institute UNS, 2025)
Laos-China relations have evolved for centuries, beginning with a tributary system that established economic and security interdependence. Although political ties were disrupted during the French colonial period and the Cold War, cross-border trade and social interactions persisted. Since the normalization of relations in the 1980s, cooperation has deepened and reached a new phase through the Laos-China High-Speed ​​Railway, a flagship project under the Belt and Road Initiative (BRI). Using a qualitative historical approach, this study examines how the Kunming-Vientiane High-Speed Railway illustrates the historical continuity and asymmetric nature of the bilateral relationship. The findings indicate that while the project enhances connectivity and supports Laos’s aspiration to become a ‘land-linked country’, it also reinforces China’s dominant position in financing, technology, and regional influence. Despite concerns about long-term dependency, the partnership remains mutually beneficial, demonstrating how BRI projects shape the dynamics between major and small states in Southeast Asia.